Nrf2 silencing to inhibit proteolytic defense induced by hyperthermia in HT22 cells - YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE BV, 2016)
Nrf2 pathway has been known to be protective against cancer progression however recent studies have revealed that the antioxidant activity of Nrf2 contributes to chemotherapy resistance. For many years, hyperthermia has been used as an additional therapy to increase the efficiency of chemotherapy and radiotherapy. Besides the positive effects of hyperthermia during treatment procedure, thermotolerance has been found to develop against heat treatment. Although the involved molecular mechanisms have not been fully clarified, heat shock proteins (HSP) and proteasome activity are known to be involved in the acquisition of thermotolerance. The aim of this study was to investigate the potential beneficial effects of combining hyperthermia with Nrf2 silencing to inhibit molecular mechanisms leading to induction of defense mechanisms in transcription level. Following heat treatment of HT22 cells, HSP70 and the proteasome levels and as well as proteasome activity were found to be elevated in the nucleus. Our results demonstrated that Nrf2 silencing reduced defense mechanisms against heat treatment both in antioxidant and proteolytic manner and Nrf2 may be a potential target for therapeutic approach in order to improve the beneficial effects of hyperthermia in cancer therapy. (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: Nrf2; Hyperthermia; Proteasome; Heat shock proteins; HEAT-SHOCK PROTEINS; UBIQUITIN-PROTEASOME PATHWAY; OXIDATIVE STRESS; BREAST-CANCER; CARCINOMA-CELLS; HELA-CELLS; INDUCTION; APOPTOSIS; ACTIVATION; HSP90